Kontroversi Ajaran Doktrin Tritunggal di Masa Kini: Urgensi Teologi Pembebasan Atau Sensasi - Georges Nicolas Djone (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of writing this article is to examine the controversy over the doctrine of the Trinity Doctrine today, as well as to analyze the relevance of the urgency of liberation theology to this teaching today, using a descriptive qualitative method approach through literature analysis and data collection techniques through Bible sources, various books and journals, as well as various documents related to the object of research. As a result, there is a massive effort to evoke Sabelianism in terms known as “Oneness Pentacostalism” today, especially in Indonesia. In conclusion, the Call for Liberation Theology and the controversy surrounding the Trinity Doctrine is not a sensation in a massive effort to evoke Sabelianism in terms known as